Effects of sugar sources and fermentation time on the properties of tea fungus (kombucha) beverage - Hasan, Belal J. Muhialdin Mula; Osman, F. A.; Muhamad, R.; Che Wan Sapawi, Che Wan Nur Safraa; Anzian, Aliaa; Voon, Wendy Wen Yi; Meor Hussin, Anis Shobirin (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2019)
Recently, fermented foods have been developing huge demand among modern consumers due to their health benefits and pleasant flavour. The objective of the present work was to evaluate the effects of fermentation time and different sugar sources on the physicochemical and antioxidant activities of kombucha tea. The sugar sources selected were white refined sugar (WRS), coconut palm sugar (CPS) and molasses sugar (MS). The fermentation substrate was boiled black tea, 10% (w/v) of each sugar, 3% (w/v) of tea fungus (SCOBY) and 10% (v/v) of previously fermented kombucha tea (back slope fermentation). The mixture was incubated in the dark at 24±3°C for 14 days. The sugar and organic acid contents were determined by HPLC, while the antioxidant active was determined by the DPPH and FRAP methods. Results demonstrated significantly higher biomass formation, glucose and sucrose content for kombucha tea fermented with WRS, while kombucha tea fermented with MS showed higher organic acid contents. Moreover, kombucha tea fermented with CPS exhibited the highest antioxidant activity and total phenolic content, followed by those fermented with MS and WRS. The present work demonstrated that kombucha tea fermented with CPS is recommended to be consumed as functional beverage for health benefits and prevention of oxidation related diseases. In addition, CPS and MS are good sugar alternatives to sucrose and other sugars frequently used in kombucha fermentation.